COMPARATIVE STUDY ON KINETIC PROPERTIES OF FREE ANDIMMOBILIZED ASPARAGINASE FROM LOCAL ISOLATE OFPseudomonase aeruginosa - Aziz, Ghazi (Iraqi Journal of Science, 2024)
The purified asparaginase from local isolate of P. aeruginosa.was immobilizedby gel entrapment using polyacrylamide,agar,sodium alginate,ionic binding onionexchanger using DEAE-cellulose and immobilized in gelatin by cross-linkingwith glutaraldehyde.The later method was the most efficient method for immobilization since theimmobilized enzyme retained about 53.5% of original activity of free enzyme. Theoptimal pH for immobilized enzyme activity was 7.5 and the enzyme was moststable at pH 6-8.5, while the values of optimal pH for activity and Stability of freeenzyme were 8.5 and (7.5-8) respectively. The immobilized enzyme retained itsoriginal activity when incubated at 25-45C° for 30 min., while the free enzymeretained its original activity after 30 min. at 25-37C°. The obtained values ofMichaelis constant (Km) and Vmax for immobilized enzyme were 0.46×10-4 M and12.2 μM/min.,respectively ,and the Km and Vmax for free enzyme were 0.25×10-4M and 16.7 μM/min,respectively. The immobilized enzyme was highly specifictowards L-asparagine and L-glutamine. The free and immobilized enzyme retainedabout 90.2% and 51% of its original activity after 3 weeks of storage at 4 C°.